Physical activity and risk of behavioural and mental health disorders in kindergarten children: analysis of a series of cross-sectional complete enumeration (census) surveys. Issue 3 (19th March 2020) - O'Brien, Kathleen; Agostino, Jason; Ciszek, Karen; Douglas, Kirsty A
Abstract : Objectives: There is mixed evidence on the relationship between physical activity and behavioural and mental health. We aimed to estimate the association between physical activity and risk of behavioural and mental health disorders in early school-aged children. Design: A series of cross-sectional complete enumeration (census) surveys. Settings: All primary schools in the Australian Capital Territory, 2014–2016. Participants: All children enrolled in their first year of full-time primary education (kindergarten) were invited to participate. Of the 16 662 eligible kindergarten children, 15 040 completed the survey for the first time. Outcome measures: Average daily physical activity participation and prevalence of risk of behavioural and mental health disorders derived from parent-reported data and the Strengths and Difficulties Questionnaire (SDQ). Characteristics associated with SDQ Total difficulties and subscales were estimated using logistic regression. Results: 8340 (61.7%) children met physical activity targets (60 min or more daily) and 709 (4.8%) were at clinically significant risk of behavioural and mental health disorders ( Total difficulties ). Known sociodemographic correlates were also those variables associated with high risk of behavioural and mental health disorders ( Total difficulties ): Aboriginal and Torres Strait Islander status (OR 2.72, 95% CI 1.78–4.16), relative socioeconomic disadvantage (most disadvantaged vs least disadvantaged, OR 1.86, 95% CI 1.38–2.50) and male sex (OR 1.80, 95% CI 1.49–2.17). Average daily physical activity was not significant, despite the highest levels of physical activity (90 min or more daily) being reported in boys, Aboriginal and Torres Strait Islander children and those from more disadvantaged areas. Conclusions: Our study provides comprehensive cross-sectional data on the relationship between physical activity participation and the risk of behavioural and mental health disorders in a large cohort of early school-aged Australian children. Aboriginal and Torres Strait Islander children, boys and those from the most disadvantaged socioeconomic group were at greatest risk of clinically significant behavioural and mental health disorders.